I hear you, forest - George, K. (Kallie), 1983- (Sounds of nature, 2021)
"The Forest has lots to say . . . if you listen. When a young child steps into the forest, her ears are open and her heart is too. She listens carefully to the forest around her--and hears such marvelous things, from the creaking of the trees stretching skyward to the rustling of the leaves sharing their secrets. This sounds-of-nature series for young children encourages imagination, awareness, and empathy with all living things. Our forests are full of magic--if we can only hear it."--